Jaguars and wild pigs indicate protected area connectivity in the south-east Atlantic Forest (Brazil) - Silva, Maite Packer [UNESP]; Massi, Klecia Gili [UNESP]; Negri, Rogerio Galante [UNESP]; Pedrosa, Felipe (Cambridge Univ Press, 2023)
The Atlantic Forest of South America has undergone major changes due to urban and agriculture/pasture extension, resulting in a highly fragmented biome. Protected areas, created to ensure the biodiversity conservation of this biome, need to be connected for long-term landscape integrity. We aimed to quantify connectivity among protected areas in the south-east Atlantic Forest using two species with different environmental requirements: a threatened species with high requirements, the jaguar Panthera onca; and an exotic species with low requirements, the wild pig Sus scrofa. Our methods included expert opinion, and Circuitscape and least-cost-path analyses. We hypothesized that the patchy and altered landscape would not support the connectivity of jaguars but would allow wild pigs to transit. In fact, we found connectivity for both species, but there were more connectivity opportunities for wild pigs. The connection between Serra do Mar (and Serra do Mar state park) and Serra da Mantiqueira (Mantiqueira Mosaic) is narrow but possible to traverse through some protected areas of sustainable use and private reserves, highlighting the importance of these to structural landscape connectivity for the studied species in this region. The same connectivity that allows the transit of the native jaguar with high environmental requirements also allows the invasive wild pig to move through the landscape, which is worrisome.
Keywords: Circuitscape; invasive species; isolation; landscape; Paraiba do Sul River Valley